Preparation method of thermal insulation material for battery and battery
By using alumina-silica sol and carboxylated cellulose hollow microspheres to modify the composite fibers of zirconia fibers in battery insulation materials, the existing materials are solved in mechanical and thermal insulation. The performance deficiency improves the thermal insulation effect of the battery, reduces the risk of thermal runaway and extends the service life.
Patent Information
- Application Number
- CN202411756250.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing battery thermal insulation materials have shortcomings in both mechanical properties and thermal insulation properties, especially in terms of poor performance in compressive stress and thermal conductivity, which is difficult to meet the battery's high-temperature management needs, which may lead to thermal runaway and safety problems.
Alumina-silica sol and carboxylated cellulose hollow microspheres are used to modify zirconia fibers to form composite fibers. Hydrogels are prepared by catalytic polycondensation, and aerogel-type thermal insulation material is formed by trimethylchlorosilane modification treatment. , enhances the bonding force between fiber and gel, and improves the dispersion and thermal insulation properties of fibers.
The good mechanical properties and thermal insulation properties of the thermal insulation materials are achieved, the uniform dispersion of fibers is enhanced, the thermal insulation effect of the battery is improved, the risk of thermal runaway is reduced, and the service life of the battery is extended.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the field of material technology, and in particular to a method for preparing a thermal insulation material for a battery and a battery. Background Art
[0002] Batteries are the core power components of new energy electric vehicles. The operating temperature of batteries is closely related to their performance, safety and service life. Inappropriate operating temperature will reduce battery capacity and shorten service life. In severe cases, thermal runaway and even explosion may occur. Therefore, thermal insulation treatment of batteries is crucial.
[0003] As for the thermal insulation of batteries, the commonly used solution is to place aerogel as a thermal insulation layer between battery cells. The molding of aerogel composite materials with good mechanical properties and thermal insulation properties has become a hot research direction, such as alumina-silicon dioxide composite aerogel materials, or adding various fibers as reinforcements. However, the molded composite materials still have great deficiencies in terms of low thermal conductivity and compressive stress, which need to be improved. Summary of the invention
[0004] To solve at least one of the above technical defects, the present invention provides the following technical solutions: The present invention discloses a method for preparing a thermal insulation material for a battery, comprising the following steps: First, prepare alumina-silica sol; Second, carboxylated cellulose hollow microspheres were used to modify zirconia fibers to form composite fibers; Third, the alumina-silica sol and the composite fiber are mixed and catalytically polycondensed to prepare a hydrogel, and the hydrogel is modified and dried to form an aerogel-type thermal insulation material.
[0005] The present invention adds composite fibers to alumina-silica aerogel, and the composite fibers serve as reinforcements to help improve gel performance. The composite fibers have zirconium oxide fibers as the main trunk and carboxylated cellulose hollow microspheres as branches. Under the action of catalytic polycondensation, the binding force between the composite fibers and the gel is enhanced, the restraining force on the gel is improved, and the sedimentation of the fibers is simultaneously reduced, so that the composite fibers are more evenly dispersed in the gel. The resulting thermal insulation material has both good mechanical properties and thermal insulation properties.
[0006] Furthermore, the composite fiber is prepared as follows: carboxylated cellulose hollow microspheres are dispersed in a solvent, and modified with an acylating agent and a silane coupling agent in sequence to obtain modified spheres; The zirconium oxide fiber and the modified sphere are mixed in a solvent and subjected to hydrolysis reaction to obtain the composite fiber.
[0007] For acylating agents, such as the common N ,N-carbonyldiimidazole, which connects the silane coupling agent to the carboxylated cellulose through an amide bond and then grafts it to the zirconia fiber through a hydrolysis reaction, helps to improve the binding force with the gel, reduce sedimentation, and then improve the dispersion of the fiber.
[0008] Furthermore, the mass ratio of carboxylated cellulose hollow microspheres, acylating agent, and silane coupling agent is 1:0.02-0.06:1-3, and the mass ratio of zirconia fiber to modified spheres is 1:2-3, which is a preferred ratio and is convenient for subsequent grafting modification with zirconia fiber.
[0009] Further, the preparation of alumina-silica sol is as follows: boric acid, aluminum chlorohydrate and tetraethyl orthosilicate are added into water and stirred to a sol state, wherein the mass ratio of boric acid, aluminum chlorohydrate and tetraethyl orthosilicate is 0.2:25-40:9-12.
[0010] Furthermore, the mass ratio of the composite fiber to the alumina-silica sol is 100:3-15, which helps to reduce the bridging between the fibers under a limited ratio and helps to improve the thermal insulation performance.
[0011] Furthermore, in the third step, the alumina-silica sol and the composite fiber are mixed and the Ph is adjusted to alkaline, and the mixture is aged at room temperature for 16-30 hours to form a hydrogel. The hydrogel is sealed with ethanol and aged at 30-55°C for 30-60 hours. The sealed ethanol is poured out and then modified with trimethylchlorosilane. In this scheme, no solvent replacement is required, which helps to reduce the number of steps.
[0012] Furthermore, the gel modified by trimethylchlorosilane is vacuum freeze-dried to obtain an aerogel type thermal insulation material.
[0013] Furthermore, the preparation of carboxylated cellulose hollow microspheres is as follows: lithium hydroxide, urea, and water are used as a solvent, cellulose is dissolved at low temperature to form a cellulose solution, the cellulose solution is dropped into liquid nitrogen to form microspheres, the microspheres are freeze-dried and then immersed in ethanol, and the hollow microspheres are formed after washing and drying; The hollow microspheres are carboxylated by using sodium periodate and sodium chlorite to obtain carboxylated cellulose hollow microspheres.
[0014] The invention discloses a battery, comprising a heat insulating material formed by the above preparation method.
[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention improves the composition of the thermal insulation material by grafting carboxylated cellulose hollow microspheres with zirconium oxide fibers. Under the action of catalytic polycondensation, the bonding force between the fibers and the gel is increased, sedimentation is reduced, and the fibers are evenly distributed in the gel. The formed aerogel thermal insulation material has both good mechanical properties and thermal insulation properties. DETAILED DESCRIPTION
[0016] The present invention will be further described below in conjunction with specific embodiments.
[0017] Example 1 A method for preparing a thermal insulation material for a battery comprises the following steps: First, prepare alumina-silica sol Boric acid, aluminum chloride hexahydrate and ethyl orthosilicate were added into water, and stirred in a water bath at 40° C. for 10 h to obtain an alumina-silica sol, wherein the mass ratio of boric acid, aluminum chloride hexahydrate, ethyl orthosilicate and water was 0.2:30:10:120.
[0018] Second, carboxylated cellulose hollow microspheres are used to modify zirconia fibers to form composite fibers Preparation of carboxylated cellulose hollow microspheres: 4% lithium hydroxide, 10% urea and 100% water are prepared into a solvent, the solvent is precooled at -40°C for 2 hours, the precooled solvent is broken into pieces, the pieces are mixed with cellulose powder at a mass ratio of 100:0.2 and stirred for 10 minutes, and the stirred material is placed at -4°C for 4 hours to dissolve at low temperature to form a cellulose solution.
[0019] The cellulose solution was dripped into liquid nitrogen through a micro-push syringe pump to form microspheres. The microspheres were freeze-dried at -50°C for 16 hours and then immersed in ethanol for 1 hour. They were washed with clean water, dried and placed in ultrapure water for 3 days. Hollow microspheres with a size of 300-600 μm were obtained.
[0020] The hollow microspheres were carboxylated with sodium periodate and sodium chlorite. Specifically, the hollow microspheres were added to a sodium periodate solution (3%), oxidized at 52°C in the dark for 30 hours, and then separated into solid and liquid. The mass ratio of the hollow microspheres to sodium periodate was 1:1.4. Sodium chlorite and acetate buffer (13 ml of acetic acid and 22 g of sodium acetate were configured into 1 L of solution) were mixed in a mass ratio of 1:50 to form a sodium chlorite solvent. The hollow microspheres modified with sodium periodate were mixed with the sodium chlorite solvent in a mass ratio of 1:2 between the hollow microspheres modified with sodium periodate and sodium chlorite, oxidized at room temperature in the dark for 24 hours, the reaction solution was dialyzed in deionized water, and the sediment was crushed to obtain carboxylated cellulose hollow microspheres.
[0021] The carboxylated cellulose hollow microspheres were added to tetrahydrofuran (200 times the mass of the carboxylated cellulose) and ultrasonically dispersed for 2 h. Then, an acylating agent (N 2000) was added at a concentration of 0.03 of the mass of the carboxylated cellulose hollow microspheres. , N-carbonyldiimidazole), stirred at 42 ° C for 3 hours, then added silane coupling agent (3-aminopropyltriethoxysilane) twice the mass of carboxylated cellulose hollow microspheres, reacted at 60 ° C for 8 hours, washed to remove the solvent and residual components, and vacuum dried at 45 ° C to obtain modified spheres.
[0022] The modified sphere was placed in an ethanol aqueous solution 200 times its mass, ultrasonicated for 2 hours, the Ph was adjusted to 5 with glacial acetic acid, zirconium oxide fiber (diameter 3-6μm, length 10-20mm) was added, the mass ratio of zirconium oxide fiber to modified sphere was 1:2, and the hydrolysis reaction was carried out at room temperature for 1.5 hours. The fiber was taken out and washed, and the washed fiber was dried at 100°C for 0.6 hours to obtain a composite fiber.
[0023] Third, the alumina-silica sol and the composite fiber were mixed and stirred for 2 hours. The mass ratio of alumina-silica sol and the composite fiber was 100:3. The Ph was adjusted to 8 with sodium hydroxide. The mixture was aged at room temperature for 20 hours. The aged sol was sealed with ethanol and then aged at 45°C for 40 hours. After the sealed ethanol was poured out, a n-hexane solution of trimethylchlorosilane (10%) was added. The mixture was sealed and kept at 25°C for 20 hours for modification reaction treatment. After washing, the modified gel was vacuum freeze-dried (-56°C, 45 hours) to obtain an aerogel-type thermal insulation material.
[0024] Example 2 A method for preparing a thermal insulation material for a battery comprises the following steps: First, prepare alumina-silica sol Boric acid, aluminum chloride hexahydrate and ethyl orthosilicate were added into water, and stirred in a water bath at 42° C. for 12 h to obtain an alumina-silica sol, wherein the mass ratio of boric acid, aluminum chloride hexahydrate, ethyl orthosilicate and water was 0.2:35:11:130.
[0025] Second, carboxylated cellulose hollow microspheres are used to modify zirconia fibers to form composite fibers Preparation of carboxylated cellulose hollow microspheres: 4.5% lithium hydroxide, 10% urea and 100% water are prepared into a solvent, the solvent is precooled at -40°C for 2 hours, the precooled solvent is broken into pieces, the pieces are mixed with cellulose powder at a mass ratio of 100:0.3 and stirred for 10 minutes, and the stirred material is placed at -4°C for 4 hours to dissolve at low temperature to form a cellulose solution.
[0026] The cellulose solution was dripped into liquid nitrogen through a micro-push syringe pump to form microspheres. The microspheres were freeze-dried at -50°C for 16 hours and then immersed in ethanol for 1 hour. They were washed with clean water, dried and placed in ultrapure water for 3 days. Hollow microspheres with a size of 300-600 μm were obtained.
[0027] The hollow microspheres were carboxylated with sodium periodate and sodium chlorite. Specifically, the hollow microspheres were added to a sodium periodate solution (3%), oxidized at 52°C in the dark for 30 hours, and then separated into solid and liquid. The mass ratio of the hollow microspheres to sodium periodate was 1:1.5. Sodium chlorite and acetate buffer (13 ml of acetic acid and 22 g of sodium acetate were configured into 1 L of solution) were mixed in a mass ratio of 1:50 to form a sodium chlorite solvent. The hollow microspheres modified with sodium periodate were mixed with the sodium chlorite solvent in a mass ratio of 1:2.2 between the hollow microspheres modified with sodium periodate and sodium chlorite, oxidized at room temperature in the dark for 24 hours, the reaction solution was dialyzed in deionized water, and the sediment was crushed to obtain carboxylated cellulose hollow microspheres.
[0028] The carboxylated cellulose hollow microspheres were added to tetrahydrofuran (200 times the mass) and ultrasonically dispersed for 1.5 h. Then, an acylating agent (N 2000, ... , N-carbonyldiimidazole), stirred at 40 ° C for 4 hours, then added silane coupling agent (3-aminopropyltriethoxysilane) with a mass 2.3 times that of carboxylated cellulose hollow microspheres, reacted at 60 ° C for 10 hours, washed to remove the solvent and residual components, and vacuum dried at 45 ° C to obtain modified spheres.
[0029] The modified sphere was placed in an ethanol aqueous solution with a volume of 260 times its mass, ultrasonicated for 1.5 hours, the Ph was adjusted to 4.5 with glacial acetic acid, zirconium oxide fiber (diameter 3-6 μm, length 10-20 mm) was added, the mass ratio of zirconium oxide fiber to modified sphere was 1:2.5, and the hydrolysis reaction was carried out at room temperature for 2 hours. The fiber was taken out and washed, and the washed fiber was dried at 100°C for 1 hour to obtain a composite fiber.
[0030] Third, the alumina-silica sol and the composite fiber were mixed and stirred for 2.5 hours. The mass ratio of alumina-silica sol and the composite fiber was 100:5. The Ph was adjusted to 8 with sodium hydroxide. The mixture was aged at room temperature for 25 hours. The aged sol was sealed with ethanol and then aged at 45°C for 35 hours. After the sealed ethanol was poured out, a n-hexane solution of trimethylchlorosilane (10%) was added. The mixture was sealed and kept at 25°C for 20 hours for modification reaction treatment. After washing, the modified gel was vacuum freeze-dried (-56°C, 50 hours) to obtain an aerogel-type thermal insulation material.
[0031] Example 3 A method for preparing a thermal insulation material for a battery comprises the following steps: First, prepare alumina-silica sol Boric acid, aluminum chloride hexahydrate and ethyl orthosilicate were added into water, and stirred in a water bath at 40° C. for 15 h to obtain an alumina-silica sol, wherein the mass ratio of boric acid, aluminum chloride hexahydrate, ethyl orthosilicate and water was 0.2:32:12:150.
[0032] Second, carboxylated cellulose hollow microspheres are used to modify zirconia fibers to form composite fibers Preparation of carboxylated cellulose hollow microspheres: 4.2% lithium hydroxide, 10% urea and 100% water are prepared into a solvent, the solvent is precooled at -40°C for 2 hours, the precooled solvent is broken into pieces, the pieces are mixed with cellulose powder at a mass ratio of 100:0.4 and stirred for 10 minutes, the stirred material is placed at -4°C for 4 hours to dissolve at low temperature to form a cellulose solution.
[0033] The cellulose solution was dripped into liquid nitrogen through a micro-push syringe pump to form microspheres. The microspheres were freeze-dried at -50°C for 16 hours and then immersed in ethanol for 1 hour. They were washed with clean water, dried and placed in ultrapure water for 3 days. Hollow microspheres with a size of 300-600 μm were obtained.
[0034] The hollow microspheres were carboxylated with sodium periodate and sodium chlorite. Specifically, the hollow microspheres were added to a sodium periodate solution (3%), oxidized at 52°C in the dark for 30 hours, and then separated into solid and liquid. The mass ratio of the hollow microspheres to sodium periodate was 1:1.5. Sodium chlorite and acetate buffer (13 ml of acetic acid and 22 g of sodium acetate were configured into 1 L of solution) were mixed in a mass ratio of 1:50 to form a sodium chlorite solvent. The hollow microspheres modified with sodium periodate were mixed with the sodium chlorite solvent in a mass ratio of 1:2.2 between the hollow microspheres modified with sodium periodate and sodium chlorite, oxidized at room temperature in the dark for 24 hours, the reaction solution was dialyzed in deionized water, and the sediment was crushed to obtain carboxylated cellulose hollow microspheres.
[0035] The carboxylated cellulose hollow microspheres were added to tetrahydrofuran (300 times of its mass) and ultrasonically dispersed for 3 h. Then, an acylating agent (N 200) accounting for 0.06 of the mass of the carboxylated cellulose hollow microspheres was added. , N-carbonyldiimidazole), stirred at 45 ° C for 2 hours, then added silane coupling agent (3-aminopropyltriethoxysilane) 3.5 times the mass of carboxylated cellulose hollow microspheres, reacted at 65 ° C for 10 hours, washed to remove the solvent and residual components, and vacuum dried at 45 ° C to obtain modified spheres.
[0036] The modified sphere was placed in an ethanol aqueous solution 200 times its mass, ultrasonicated for 2 hours, the Ph was adjusted to 4 with glacial acetic acid, zirconium oxide fiber (diameter 3-6 μm, length 10-20 mm) was added, the mass ratio of zirconium oxide fiber to modified sphere was 1:2.6, and the hydrolysis reaction was carried out at room temperature for 1 hour, the fiber was taken out and washed, and the washed fiber was dried at 100°C for 1.5 hours to obtain a composite fiber.
[0037] Third, the alumina-silica sol and the composite fiber were mixed and stirred for 2 hours. The mass ratio of alumina-silica sol and the composite fiber was 100:8. The Ph was adjusted to 8 with sodium hydroxide. The mixture was aged at room temperature for 20 hours. The aged sol was sealed with ethanol and then aged at 45°C for 40 hours. After the sealed ethanol was poured out, a n-hexane solution of trimethylchlorosilane (10%) was added. The mixture was sealed and kept at 25°C for 20 hours for modification reaction treatment. After washing, the modified gel was vacuum freeze-dried (-56°C, 45 hours) to obtain an aerogel-type thermal insulation material.
[0038] Comparative Example 1 Compared with Example 1, the difference is that: in this example, there is no grafting process of carboxylated cellulose hollow microspheres and zirconia fibers, and equal masses of carboxylated cellulose hollow microspheres and zirconia fibers are added to the sol independently.
[0039] Comparative Example 2 Compared with Example 1, the difference is that the composite fiber in this example is formed by carboxylated cellulose nanofibers grafted onto zirconia fibers, and the quality of the carboxylated cellulose nanofibers and zirconia fibers is consistent with that of the carboxylated cellulose hollow microspheres and zirconia fibers in Example 1.
[0040] The performance of the thermal insulation material prepared above was tested, as shown in Table 1: Table 1
[0041] From the data in the above table, it can be seen that the grafting modification of carboxylated cellulose hollow microspheres on zirconia fibers, the alkaline polycondensation makes the in-situ combination of alumina and fibers, the uniformity of fiber dispersion and the skeleton support in the gel make the formed thermal insulation material excellent in thermal conductivity and compressive stress, and is worthy of promotion and application.
[0042] The above are only preferred embodiments of the present invention. The protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a thermal insulation material for a battery, characterized in that: The following steps are involved: First, prepare alumina-silica sol; Second, carboxylated cellulose hollow microspheres were used to modify zirconia fibers to form composite fibers; Third, the alumina-silica sol and the composite fiber are mixed and catalytically polycondensed to prepare a hydrogel, and the hydrogel is modified and dried to form an aerogel-type thermal insulation material.
2. The method for preparing a thermal insulation material for a battery according to claim 1, characterized in that: The composite fiber is prepared as follows: carboxylated cellulose hollow microspheres are dispersed in a solvent, and modified with an acylating agent and a silane coupling agent in sequence to obtain modified spheres; The zirconium oxide fiber and the modified sphere are mixed in a solvent and subjected to hydrolysis reaction to obtain the composite fiber.
3. The method for preparing a thermal insulation material for a battery according to claim 2, characterized in that: The mass ratio of carboxylated cellulose hollow microspheres, acylating agent and silane coupling agent is 1:0.02-0.06:1-3, and the mass ratio of zirconia fiber to modified sphere is 1:2-3.
4. The method for preparing a thermal insulation material for a battery according to claim 1, wherein: The preparation of alumina-silica sol is as follows: boric acid, aluminum chlorohydrate and tetraethyl orthosilicate are added into water and stirred to a sol state, wherein the mass ratio of boric acid, aluminum chlorohydrate and tetraethyl orthosilicate is 0.2:25-40:9-12.
5. The method for preparing a thermal insulation material for a battery according to claim 1, characterized in that: The mass ratio of the composite fiber to the alumina-silica sol is 100:3-15.
6. The method for preparing a thermal insulation material for a battery according to claim 1, characterized in that: In the third step, the alumina-silica sol and the composite fiber are mixed and the Ph is adjusted to alkaline, and the hydrogel is aged at room temperature for 16-30 hours to form the hydrogel. The hydrogel is sealed with ethanol and aged at 30-55°C for 30-60 hours. The sealed ethanol is poured out and modified with trimethylchlorosilane.
7. The method for preparing a thermal insulation material for a battery according to claim 6, characterized in that: The gel modified by trimethylchlorosilane is vacuum freeze-dried to obtain an aerogel type thermal insulation material.
8. The method for preparing a thermal insulation material for a battery according to claim 1, characterized in that: The preparation of carboxylated cellulose hollow microspheres is as follows: lithium hydroxide, urea and water are used as a solvent, cellulose is dissolved at low temperature to form a cellulose solution, the cellulose solution is dropped into liquid nitrogen to form microspheres, the microspheres are freeze-dried and then immersed in ethanol, and the hollow microspheres are formed after washing and drying; The hollow microspheres are carboxylated by using sodium periodate and sodium chlorite to obtain carboxylated cellulose hollow microspheres.
9. A battery, characterized in that: The invention relates to a thermal insulation material formed by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Nano-crystalline cellulose fiber high in carboxyl group content and preparation and application thereof
CN105463606A
Preparation method of natural macromolecular hollow microspheres
CN106633113A
Nanometer cellulose reinforced silica gel composite material and preparation method thereof
CN107337423A
Preparation method of microcrystalline cellulose / Al2O3-SiO2 composite aerogel
CN116003870A
Silicon-aluminum-based aerogel fiber composite material and preparation process thereof
CN116375447A
